Effects of a mindfulness-based health promotion program on mindfulness, psychological capital, compassion fatigue, and affect in healthcare workers - Quiroz-González, Eliana; Lupano Perugini, María Laura; Delgado-Abella, Leonor Emilia; Arenas-Granada, Jaime; Demarzo, Marcelo (Frontiers in Psychology, 2024)
Objective This study aimed to examine the effects of the Mindfulness-Based Health Promotion program on mindfulness, psychological capital, compassion fatigue, and affect in a sample of healthcare workers at a hospital in Colombia. Method Randomized controlled study with pre-test and post-test measures, in which 33 workers participated (Mage = 35.01, SD = 10.0), assigned to the experimental group (EG, n = 16, Mage = 34.00, SD = 9.59) and the wait-list control group (CG, n = 17, Mage = 36.03, SD = 10.56). The contrast of the program effects was carried out through a mixed factorial ANOVA. Results We found significant effects on observing, non-reacting and mindfulness as a function of the group factor. Conclusion We concluded the Mindfulness-Based Health Promotion program showed positive effects on mindfulness, this was tested with a novel program designed for the Latin population. This study is pioneering in using this mindfulness program in Colombia. These findings offer valuable insights for leaders of healthcare institutions when developing intervention programs that promote the mental health in the workplace. Future studies with larger samples and mixed-methods are necessary to confirm our results and to identify factors that can predict these findings.